Development of Rubber Media Based Resistance Model for Sprint Runners in Riau - Septiandi Eka Putra; Johansyah Lubis; Novi Marlina Siregar (research, training and philanthropy institution Natural Aceh, 2021)
The aim of this study is to develop a rubber-based resistance training model for sprint athletes in Riau province by evaluating the efficacy of increasing sprint athletes' short distance running pace. The research method used in this study is ADDIE's research and development method, which consists of five steps. Athletes from Riau Province participated in this study as test subjects. analysis, design, development, implementation, and evaluating are the first steps in the research process. Three experts were present for the model feasibility test: two athletic lecturers and one national athletic coach. The model's efficacy was tested using a 60-meter speed parameter test involving 30 athletes from Riau Province, 15 of whom were in the experimental group and 15 of whom were in the control group. The difference test results from SPSS 22 showed that the experimental group had an average difference of 0.78 and the control group had an average difference of 0.12. The discrepancy is derived from the test results, which are expressed in terms of time, so the shorter the time, the better. The discrepancy between the experimental and control groups' different values, or mean different = 0.658, t-count = 23.632, df = 28, with p-value = 0.000 < 0.05, indicates that there are substantial variations between the experimental and control groups. It can be concluded that the rubber media-based Resistance training model for Riau provincial sprint athletes is more successful and can help the Riau provincial sprint athletes improve their 100-meter running pace